Learning mathematics without stress: Tips and tricks for effective mathematics learning - Salsabila, Dani Dwi (Maliki Interdisciplinary Journal, 2024)
This research provides insights into effective methods of learning mathematics. Qualitative methods are employed in this study to outline and provide clear and concise explanations of tips and tricks in learning mathematics, including determining study time and location, taking notes and understanding formula concepts, using memory and analytical techniques, forming study groups, daring to ask questions, utilizing varied sources, and frequently practicing problem-solving. By applying these tips and tricks, it is hoped that readers can enhance their mathematical skills in an enjoyable manner and without pressure.